Development of Learning Media Based on Scratch Educational Games for Straight Line Equation - Jarilla Syahdita Azza Nehro Al Amirus Salma; Indah Wahyuni (Universitas Syiah Kuala, 2025)
Rapid technological developments in the 21st century have encouraged the use of digital media in mathematics learning. Using technology-based interactive learning materials is one way to enhance student learning results. This study was conducted at a public junior high school in Rambipuji, Jember, East Java, Indonesia, to develop and test Fly and Count, a Scratch-based learning medium that is valid, practical, and effective in enhancing learning outcomes. The ADDIE development model, which comprises the phases of analysis, design, development, implementation, and evaluation, was applied in this study. A validation sheet, a practicality questionnaire, and a learning outcome test on the subject of straight line equation were among the tools utilized. The results showed that the media was highly valid according to subject matter experts (87.14%) and valid according to media experts (66.66%). The practicality test showed very practical responses from teachers (88%) and students (90.33%). The effectiveness test showed an increase in student learning outcomes with an N-Gain score of 0.69 (moderate category). Thus, Fly and Count is declared valid, practical, and effective for use as a learning medium for straight line equation.